2016
DOI: 10.1007/s13671-016-0135-8
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient and Tertiary Consultations in Teledermatology

Abstract: Inpatient and tertiary teledermatology have significant potential to increase access to timely, high-quality, specialized dermatology care. Early studies on inpatient teledermatology suggest that it is reliable and can provide assistance with both triage and management decisions, making it a potentially valuable adjunct to increase access to inpatient dermatology care. Initial studies on tertiary teledermatology suggest that it is a popular modality of care, both formally and informally, and that it can reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Although both models can be considered highly cost-effective, herein, it has been found that teledermatology reduces costs and is satisfactory to both patients and professionals. Reviews, such as those by Barbieri et al [ 32 ], agree that TD has the potential to provide access to suitable, quality care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although both models can be considered highly cost-effective, herein, it has been found that teledermatology reduces costs and is satisfactory to both patients and professionals. Reviews, such as those by Barbieri et al [ 32 ], agree that TD has the potential to provide access to suitable, quality care.…”
Section: Discussionmentioning
confidence: 99%
“…Zakaria [ 24 ] demonstrated that TD favours the remote classification and treatment of patients with dermatological conditions by means of implementing a triage system, which in turn contributes to a reduction of costs. The study by Barbieri et al [ 32 ] also suggests that TD is effective for classification in dermatological consultations and could increase their efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation